Analysis of Factors Affecting Business Performance: Empirical Study of Hospitals in East Java - Afifi, M. Fiyan; Murhadi, Werner Ria (Journal of Entrepreneurship & Business, 2023)
Purpose: Hospitalization in Indonesia continued to increase by 5.2% per year in 2018, with the most significant number of hospitals in Indonesia being in the province of East Java. However, Indonesia is the most important contributor to overseas medical visits. Total expenses reach IDR 161 trillion/year (US$ 11.5 billion/year), and 80% of visits are to Malaysia, where every year, million Indonesian citizens (WNI) seek treatment abroad. Of this amount, the total costs incurred reached IDR 97 trillion. This becomes a question, what triggers Indonesian citizens to seek treatment abroad? This study aims to analyze the factors that influence business performance in hospitals in East Java. Methods: This study used a purposive sampling technique with a total sample of 62 respondents. Respondents in this study were hospital leaders in East Java. This study uses a quantitative approach with the analysis in this study using Smart PLS. Result: the results show that environmental uncertainties hurt the business performance of the hospital. This result is due to environmental uncertainties being a broad factor, difficult to predict either individually or collectively. However, environmental uncertainties have a significant positive effect on strategic orientation. Environmental uncertainties have a negative and significant effect on managerial capability. Meanwhile, strategic direction and managerial capability have a positive and significant effect on the business performance of hospitals in East Java.